PERBAIKAN PERKECAMBAHAN DAN PERTUMBUHAN BAWANG MERAH DENGAN PERENDAMAN BENIH DALAM GIBERELIN - Agus Nugroho Setiawan; Kurniawan Vistiadi; Sarjiyah Sarjiyah (Politeknik Negeri Lampung., 2021)
Shallots are mostly developed with tubers as planting material, even though they have many disadventages. An alternative that can be done is to use seeds in the form of botanical seeds (True Shallot Seed/TSS), but there is still a long nursery time. This study aims to obtain the concentration and soaking time of the gibberellin on the germination and growth of shallot seedlings. The research was conducted using a single factor experimental method that arranged in a completely randomized design. The treatments were 4 gibberellins concentrations i.e. 2, 4, 6 and 8 ppm which were immersed for 12 and 24 hours, with 3 replications and each replication consisted of 5 sample. The observed variables were germination, vigor index, height of plant, number of leaves, leaf area, fresh weight and dry weight of seedling. The results of the research showed that a gibberellin with a concentration of 2 ppm with soaking time of 24 hours was able to increase the germination and vigor index of shallot seeds, and as well as increase the growth of shallot seedlings.